“We find that…” changing patterns of epistemic positioning in research writing - Yang, Yanfang; Guo, Xuan (Frontiers in Psychology, 2025)
IntroductionEpistemic positioning refers to the writer’s commitment to the truth of a proposition and assessment of its potential impact on readers. Despite its importance, little attention has been paid to how writers make epistemic judgments across disciplines over time.MethodsDrawing on Hyland and Zou’s taxonomies of hedges and boosters, we analyzed 240 research articles from education, history, mechanical engineering, and physics, covering three periods (1960, 1990, and 2020).ResultsOur findings show that epistemic positioning has significantly decreased across all four disciplines over time, with writers increasingly preferring less use of epistemic markers in pursuit of an objective, data-based, and scientific style.DiscussionThese results suggest a disciplinary shift in research writing practices and have important implications for raising students’ and novice academic writers’ awareness of evolving knowledge discourses shaped by changing societies.